Dominant-Negative Synthesis Suppression of Voltage-Gated Calcium Channel Ca(v)2.2 Induced by Truncated Constructs - Raghib, Ayesha (J Neurosci, 2001)
Voltage-gated calcium channel α1 subunits consist of four domains (I–IV), each with six transmembrane segments. A number of truncated isoforms have been identified to occur as a result of alternative splicing or mutation. We have examined the functional consequences for expression of full-length Ca(v)2.2 (α1B) of its coexpression with truncated constructs of Ca(v)2.2. Domains I-II or domains III-IV, when expressed individually, together with the accessory subunits β1b and α2δ-1, did not form functional channels. When they were coexpressed, low-density whole-cell currents and functional channels with properties similar to wild-type channels were observed. However, when domain I-II, domain III-IV, or domain I alone were coexpressed with full-length Ca(v)2.2, they markedly suppressed its functional expression, although at the single channel level, when channels were recorded, there were no differences in their biophysical properties. Furthermore, when it was coexpressed with either domain I-II or domain I, the fluorescence of green fluorescent protein (GFP)–Ca(v)2.2 and expression of Ca(v)2.2 protein was almost abolished. Suppression does not involve sequestration of the Ca(v)β subunit, because loss of GFP–Ca(v)2.2 expression also occurred in the absence of β subunit, and the effect of domain I-II or domain I could not be mimicked by the cytoplasmic I-II loop of Ca(v)2.2. It requires transmembrane segments, because the isolated Ca(v)2.2 N terminus did not have any effect. Our results indicate that the mechanism of suppression of Ca(v)2.2 by truncated constructs containing domain I involves inhibition of channel synthesis, which may represent a role of endogenously expressed truncated Ca(v) isoforms.